Local Upland Rice Varieties, Solutions to Food Security in Dry Land - syahril, muhammad syahril; Siregar, Dolly Sojuangan (Jurnal Online Pertanian Tropik, 2023)
Indonesia is an agricultural country with the fourth largest population in the world. However, climate change is having a major impact on agricultural production due to increased dry land. For effective agricultural disaster management, it is important to understand and measure drought in rice crop production. The research was conducted by designing a drought agro-ecosystem using PEG 6000. Eleven local upland rice varieties were tested with two sensitive varieties and one tolerant upland rice variety as a comparison. The study was designed using a randomized block design with five replications and tested with an analysis of variance using the contrast method. The results showed that local varieties were more tolerant to drought abiotic stress when compared to inbreed and hybrid varieties. Local varieties showed non significant differences with the varieties recommended for dry land.